Theory of elastic stability - Timoshenko, Stephen, 1878-1972 (Dover Publications, 2009)
The best available guide to the elastic stability of large structures, this volume was co-authored by world-renowned authorities on engineering mechanics. It ranges from theoretical explanations of 2- and 3-D stress and strain to practical applications such as torsion, bending, thermal stress, and wave propagation through solids. Equally valuable as text or reference. 1961 edition.
Originally published: New York : McGraw Hill Book, 1961.
Keywords: Elasticity.; Strains and stresses.; elektronické knihy; electronic books